Basics for sensorimotor information processing: some implications for learning - Vidal, Franck; Meckler, Cédric; Hasbroucq, Thierry (Frontiers in Psychology, 2015)
Abstract In sensorimotor activities, learning requires efficient information processing; whether in car driving, sport activities or human-machine interactions. Several factors may affect the efficiency of such processing: they may be extrinsic (i.e. task-related) on intrinsic (i.e. subjects-related). The effects of these factors are intimately related to the structure of human information processing. In the present article we will focus on some of them, which are poorly taken into account, even when minimizing errors or their consequences is an essential issue at stake. Among the extrinsic factors, we will discuss, first, the effects of the quantity and quality of information, secondly, the effects of instruction and thirdly motor program learning. Among the intrinsic factors, we will discuss first the influence of prior information, secondly how individual strategies affect performance and, thirdly, we will stress the fact that although the human brain is not structured to function errorless (which is not a new) humans are able to detect their errors very quickly and (in most of the cases), fast enough to correct them before they result in an overt failure.